2018
DOI: 10.1007/s00038-018-1136-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual violence in Brazil: associated individual and contextual factors

Abstract: Sexual violence is more prevalent in federal units that presented lower years of schooling expectancy at 18 years old (PR 1.27; CI95% 1.09-1.48), lower per capita income (PR 1.23; CI95% 1.05-1.43), lower HDI (PR 1.17; CI95% 1.01-1.37), higher proportion of poverty vulnerability (PR 1.18; CI95% 1.02-1.38), higher proportion of unemployment (PR 1.68; CI95% 1.45-1.96) and higher proportion of people who neither work nor study (PR 1.26; CI95% 1.08-1.46). Higher prevalence of sexual violence was associated with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
12
0
4
Order By: Relevance
“…Similarly, the construct of disparity conditions was discussed in regard to personal financial struggles, which aligns with literature stating that unemployment and lower income have been linked to IPV [8]. Moreover, sexual violence has been found to be more common in areas with lower education, lower income, and higher unemployment in Brazil [26]. Participants described gendered patterns of violence and one participant explicitly articulated the role of sexism in gender-based violence, which suggests that underlying sexism may be considered a disparity condition in syndemic models.…”
Section: Evidence For Syndemic Social Comorbiditiesmentioning
confidence: 54%
“…Similarly, the construct of disparity conditions was discussed in regard to personal financial struggles, which aligns with literature stating that unemployment and lower income have been linked to IPV [8]. Moreover, sexual violence has been found to be more common in areas with lower education, lower income, and higher unemployment in Brazil [26]. Participants described gendered patterns of violence and one participant explicitly articulated the role of sexism in gender-based violence, which suggests that underlying sexism may be considered a disparity condition in syndemic models.…”
Section: Evidence For Syndemic Social Comorbiditiesmentioning
confidence: 54%
“…It is clearly observed that girls are the most affected. In almost all the studies, the number of girls who suffered a sexual abuse was bigger than the number of boys [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In the social context, these cases are permeated by misconceptions regarding gender identity or sexual orientation of the victim, contributing to a lesser visibility of male sexual abuse as a public health problem [13]. Besides that, da Silva & Roncalli [2] affirm that men tend to have less access to health services when compared to women. Although a tremendous amount of men suffers this type of violence, women are still the main victims in all age groups whichcharacterizes a marked gender violence [12].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of marriage in Switzerland is 30 years and the mean age in our sample was <26 years. Moreover, in low-and middle-income countries, low income and education levels as well as higher rates of forced marriage under the age of 18 years have been shown to be independent risk factors of sexual violence, particularly against minors [6,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%